Electronic properties of 6,13-diazapentacene adsorbed on Au(111): a quantitative determination of transport, singlet and triplet states, and electronic spectra - Ajdari, Mohsen; Schmitt, Tanja; Hoffmann, Marvin; Maaß, Friedrich; Reiß, Hilmar; Bunz, Uwe H. F.; Dreuw, Andreas; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
The electronic structure of organic/metal interfaces and thin films is essential for the performance of organic-molecule-based field effect transistors and solar cells. Here, we investigated the adsorption and electronic properties of the N-heteropolycyclic aromatic compound 6,13-diazapentacene (DAP), a potential electron-transporting semiconductor on Au(111), using temperature-programmed desorption, vibrational and electronic high-resolution electron energy loss spectroscopy, two-photon photoemission spectroscopy, and state-of-the-art quantum chemical methods. In the mono and multilayer regime DAP adsorbs in a planar fashion with the molecular backbone oriented parallel to the gold substrate. The energetic position of transport levels (electron affinities and ionization potentials) and singlet (S) as well as triplet (T) transition energies are quantitatively determined. The lowest affinity level is located at 3.48 eV, whereas the energetic position of the first excitonic state is at 4.00 eV, resulting in an exciton binding energy of 0.52 eV. Compared to pentacene, the optical gap is reduced by 0.1 eV and the a-band gains substantially in intensity, which is explained by a detailed analysis of the electronic structure. The optical gap, i.e., the S-1 excitation energy, is determined to be 2.0 eV, and the T-1 transition energy is 0.9 eV, making an exothermic singlet fission process relevant in organic photovoltaics feasible.